28.4k views
1 vote
Given x=-3, y=6, and z=-4
-15+(-x)+y=

1 Answer

3 votes

Answer:

-6

Explanation:

We are given x=- 3 , y= 6 and z= -4.

We are also given the expression:

-15 + (-x) +y

Substitute -3 in for x and 6 in for y.

-15 + (- -3) + 6

2 negative signs creates a positive sign

-15 + (+3) +6

-15 + 3+ 6

Add -15 and 3.

(-15+3) +6

-12 +6

Add -12 and 6.

-6

-15+(-x)+y evaluated at x= -3 and y=6 is equal to -6.

User LeeNeverGup
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.